KEPUTUSAN PETANI DALAM USAHATANI PADI ORGANIK DI KABUPATEN BANTUL - Triyono, Triyono (Berkala Ilmiah AGRIDEVINA, 2014)
As a manager in farming, farmers have a role in making decisions on the implementation of the farm is run. This study aims to reveal the decisions of farmers in organic rice farming, and analyzes the factors that influence it. The study was conducted in seven districts of organic rice development center in Bantul. Data collected through interviews and observations of the 140 members of farmer groups are considered the most active. Data were analyzed using multinomial logit model and Tobit. The results showed Decision rice farmers in Bantul influenced by education, experience and tenure status.